Modul Praktikum Berbasis Projek Pemilah Logam Berdasarkan Berat Termonitoring Iot Berbasis Scada - Hasan Hasan; Irawan Suharto; Medi Yuwono Tharam (Jurusan Teknik Elektro Politeknik Negeri Pontianak, 2023)
Trainer modules based on industrial control operation processes will make it easy for students or learners to understand the concept of using industrial control in real applications. Especially for engineering fields such as electrical engineering, especially the field of industrial automation. To explore the abilities of students more deeply, a module in the research entitled